“Gestión financiera y su impacto en la recuperación de cartera del Banco Amibank, del cantón Quevedo. Período 2022-2023” - Paredes Figueroa, William Vicente (2025)
This research arises from the need to understand how financial management affects the recovery of overdue loans in banking institutions, using Banco Amibank, Quevedo branch, as a case study. The study analyzed the implementation of regulatory practices related to the monitoring of delinquent loans, credit risk assessment, accounting provisions for losses, and operational strategies to improve asset recovery. A mixed-method approach was used, with a non-experimental design and descriptive level. Data were collected through interviews with bank staff and surveys administered to clients with overdue loans. The findings show that, in general, the practices align with institutional guidelines, but also reveal operational deviations such as the use of refinancing mechanisms and discount campaigns not formally established in policy. It was also identified that the actual causes of default observed in the field are not always reflected in institutional reports, weakening the accuracy of decision-making. The strategies implemented have led to positive impacts in terms of recovery times and levels, although challenges remain in follow-up and post-restructuring control. It is concluded that improving financial management requires not only formal compliance but also strategic adaptation to the real conditions of the loan portfolio, strengthening evaluation mechanisms, accounting records, and client support to achieve sustainable recovery.